2020
DOI: 10.1186/s12885-020-07093-9
|View full text |Cite
|
Sign up to set email alerts
|

Design and methods of a national, multicenter, randomized and controlled trial to assess the efficacy of a physical activity program to improve health-related quality of life and reduce fatigue in women with metastatic breast cancer: ABLE02 trial

Abstract: Background: Patients with a metastatic breast cancer suffer from a deteriorated health-related quality of life and numerous symptoms such as pain, severe fatigue and a decrease of their physical fitness. As the feasibility of a physical activity program has been demonstrated in this population, ABLE02 aims to assess the efficacy of a 6 month-physical activity program using connected devices to improve health-related quality of life and to reduce fatigue in women with metastatic breast cancer. Methods: ABLE02 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 84 publications
0
11
0
Order By: Relevance
“…For mind-body interventions, this was the case in 4/7 interventions (Lengacher et al, 2018;Mikolasek et al, 2021;Price-Blackshear et al, 2020;Zernicke et al, 2014) and with regard to the psychological interventions, 9/13 found a significant effect on CRF (Abrahams et al, 2017;Bray et al, 2017;Dozeman et al, 2017;Henry et al, 2018;Owen et al, 2017;Ritterband et al, 2012;van den Berg et al, 2015; Almost all interventions were for patients after primary treatment. Five interventions were delivered only during primary treatment; these were one physical activity intervention (Delrieu, Anota, et al, 2020), two mind-body interventions (Carlson et al, 2019;Kubo et al, 2018) and two interventions of the combined category (Grossert et al, 2016;Zhou et al, 2020). Four interventions were delivered to patients both during and after treatment; these were one mind-body intervention (Mikolasek et al, 2021), one psychological intervention (Owen et al, 2017) and two in the combined category (Smith et al, 2019;Spahrkäs et al, 2020a).…”
Section: Study Results (Effectiveness)mentioning
confidence: 99%
See 1 more Smart Citation
“…For mind-body interventions, this was the case in 4/7 interventions (Lengacher et al, 2018;Mikolasek et al, 2021;Price-Blackshear et al, 2020;Zernicke et al, 2014) and with regard to the psychological interventions, 9/13 found a significant effect on CRF (Abrahams et al, 2017;Bray et al, 2017;Dozeman et al, 2017;Henry et al, 2018;Owen et al, 2017;Ritterband et al, 2012;van den Berg et al, 2015; Almost all interventions were for patients after primary treatment. Five interventions were delivered only during primary treatment; these were one physical activity intervention (Delrieu, Anota, et al, 2020), two mind-body interventions (Carlson et al, 2019;Kubo et al, 2018) and two interventions of the combined category (Grossert et al, 2016;Zhou et al, 2020). Four interventions were delivered to patients both during and after treatment; these were one mind-body intervention (Mikolasek et al, 2021), one psychological intervention (Owen et al, 2017) and two in the combined category (Smith et al, 2019;Spahrkäs et al, 2020a).…”
Section: Study Results (Effectiveness)mentioning
confidence: 99%
“…The Patient-Reported Outcomes Measurement Information System (PROMIS,Henry et al, 2018;Kelleher et al, 2021;Mikolasek et al, 2018;Nápoles et al, 2019;Price-Blackshear et al, 2020;Subnis et al, 2020) and the Functional Assessment of Cancer Therapy (FACT) or Functional Assessment of Chronic Illness Therapy (FACIT,Bray et al, 2017;Carlson et al, 2019;Grossert et al, 2016;Puszkiewicz et al, 2016;Smith et al, 2019;Zachariae et al, 2018) was used in six interventions. FACT and FACIT are the same as the questionnaire started as FACT and continued later as FACIT(Webster et al, 2003).We found five (14%) physical activity interventions, which included exercises and activity goal setting(Table 3, Bruggeman- Everts et al, 2017;Delrieu et al, 2018;Delrieu, Anota, et al, 2020;Falz et al, 2021;Galiano-Castillo et al, 2013Puszkiewicz et al, 2016;Wolvers, 2017;. The seven (20%) mind-body interventions were almost all mindfulnessbased and are outlined in Table 4(Carlson et al, 2019;Kubo et al, 2018;Lengacher et al, 2018;Mikolasek et al, 2018Mikolasek et al, , 2021Price-Blackshear et al, 2020;Subnis et al, 2020;Zernicke et al, 2014Zernicke et al, , 2013Zernicke et al, , 2016.…”
mentioning
confidence: 86%
“…Trackers have been used in a randomised controlled trial to encourage patients with mNSCLC to maintain their PA by recommending a targeted number of steps 76. In a previous study by the team, the use of activity trackers has shown pertinent results in women with metastatic breast cancer 77 78. The combination of these two intervention modalities (acute exercise and unsupervised walking programme) allows us to offer an intervention adapted to this population in order to have sufficient physiological stimulation to observe changes in the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Al Maqbali et al of 129 clinical trials conducted between 1993 and 2020 estimated that 60.6% of patients with advanced breast cancer experienced fatigue [ 11 ]. Fatigue is common among those who have been treated with chemotherapy, immunotherapy, or hormone therapy [ 12 ], and can be associated with the site of metastasis [ 13 , 14 ]. While fatigue is inherently difficult to quantify, studies employ questionnaires beginning at the time of treatment and continuing at fixed intervals afterward to identify chronic treatment-related symptoms.…”
Section: Discussionmentioning
confidence: 99%